Evaluation of cucumber genotypes under plastic house and open field conditions in Lalitpur, Nepal - Sujan Subedi; Nirajan Bhandari; Manoj Basnet; Navin Gopal Pradhan; Ishwori Prasad Gautam (Cogent Food & Agriculture)
The low production of cucumber (Cucumis sativus L.) in Nepal is associated with the lack of high-yielding gynoecious hybrids, the long gestation period and low yields of open-pollinated varieties and cold stress in open field conditions during the off-season. An experiment was conducted at the National Horticulture Research Centre, Nepal Agricultural Research Council, Khumaltar, Lalitpur, Nepal, from February to July 2019 to evaluate the performance of cucumber genotypes under open field and plastic house conditions. The experiment was laid out in a two-factor randomized complete block design (RCBD) with seven genotypes (Bhaktapur Local, HRDCUC-004 × HRDCUC-001, HRDCUC-004 × HRDCUC-003, HRDCUC-006 × HRDCUC-001, HRDCUC-006 × HRDCUC-003, HRDCUC-009 × HRDCUC-001, and HRDCUC-009 × HRDCUC-003) and two growing conditions (open field and plastic house). Genotypes and growing conditions affected yield and yield attributing characters. Genotype HRDCUC-004 × HRDCUC-001 grown under the plastic house was superior in terms of the number of fruits plant−1 (28.33), yield plant−1 (12.43 kg), and adjusted yield hectare−1 (117 t ha−1). The highest benefit-cost ratio (2.99:1) was also observed for the genotype HRDCUC-004 × HRDCUC-001 grown under plastic house conditions. Overall acceptability of consumers was higher in genotype Bhaktapur Local (7.6) followed by HRDCUC-004 × HRDCUC-001 (7.2). Cucumber genotype HRDCUC-004 × HRDCUC-001 was promising for yield and yield attributing characters under both growing conditions.PUBLIC INTEREST STATEMENTCucumber, a globally popular vegetable crop, holds significant economic importance and is widely used in kitchens as a salad. Despite the availability of many exotic hybrid varieties, Nepal struggles with low cucumber production. Therefore, it is crucial to evaluate the performance of gynoecious hybrid cucumber varieties in terms of yield, quality, and maturity to meet the national demand. Additionally, ensuring year-round cucumber production is essential to guarantee its availability in the market. The production of high yielding gynoecious cucumber hybrids within protected structures such as plastic houses could be a feasible option to fulfill the domestic demand and ensure year-round availability in the market..